Pelatihan Bagi Kader Posyandu Penyakit Tidak Menular (PTM) - Lilis Lismayanti; Ida Rosidawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2018)
The Healthy Indonesia Program aims to improve health status through health efforts and equitable health services. The positive side of the success of health development is the increasing life expectancy. But it has a negative impact, namely the increasing incidence of degenerative diseases, one of which is hypertension. Hypertension is often called the